An Energy-Autonomous Power-and-Data Telemetry Circuit With Digital-Assisted-PLL-Based BPSK Demodulator for Implantable Flexible Electronics Applications - Luominghao Pan (IEEE, 2021)
Wireless power transmission and data telemetry technology has been widely adopted in healthcare applications based on flexible electronics. It is challenging to achieve high data rate (up to Mbps), low bit-error-rate (BER< 0.1%) data telemetry, as well as simultaneous high energy-efficiency power transmission, with small-volume flexible devices. In this paper, an energy-autonomous power-and-data telemetry circuit with digital-assisted-phase lock loop (PLL)-based binary-phase-shift-keying (BPSK) demodulator for implantable flexible electronics applications has been proposed. Only a single pair of coils has been employed to transmit both power and data based on a BPSK modulated Class-E amplifier. The energy recovery circuit enables a battery-less energy-autonomous implantable device. The proposed digital-assisted control circuitry resets the PLL to maintain the lock state and demodulate the BPSK data. As a result, the maximum data rate is no longer limited by the PLL’s bandwidth, which can be improved significantly. The chip has been implemented with standard 180nm CMOS process, occupying an area of 0.96 mm2. The post-layout simulation shows up to 2.26 Mbps data rate can be achieved with a low BER less than 8.6x10−5 with the coupling factor ranging from 0.13 to 0.17. Thanks to the digital-assisted-PLL-based demodulator, the power consumption of the receiver is only $817.4 ~μ \text{W}$ and the demodulator Figure-of-Merit (FoM) is 362 pJ/bit with 13.56 MHz carrier frequency. The energy-autonomous circuit based on a single and small-volume pair of coils demonstrates its potential capability to be applied to various kinds of implantable biomedical applications.